HERMENEUTIKA SEBAGAI INSTRUMEN ALTERNATIF UNTUK MENAFSIRKAN AL-QUR’AN - Waliko Waliko (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2021)
The Qur'an, as the holy book of the Muslims and also as a guide to life, has been, is, and will always be interpreted. Therefore, in the view of Muslims, the interpretation of the Quran is a very established term. The Quran is considered a limited text, while man changes according to the development of the times. So, the Qur'an urgently needs to be interpreted based on the needs of modern humans today. The development of the interpretation of the Quran is increasingly complex, and following the times as the expression shalih li kulli zaman, wa makan is inevitable. So, the interpretation that should be centered on the Quran and Sunnah is the wisest path, but from the diversity of different interpretations, giving rise to various interpretations according to the text, context, and contextual. Until the interpretation of the Quran by the classical scholars has provided solutions to various problems they face, both godly questions and humanitarian issues. Because the various problems faced by each mufassir are different, the quranic message that was born is different and plural—the opinion of classical scholars who have the best interpretation authority. Be a reason to try to elaborate on the urgency of the need of the Quran against hermeneutics as one solution to the monotonous study of the scholars of earlier interpretations to gain new enlightenment offered by contemporary thinkers. This offer tries to construct the interpretation products of classical interpreters not to cover any new contributions that can answer the problems of modern society today. According to the frugal author, hermeneutics can still be used as one of the instruments in the method of interpretation, provided; first, a hermeneutic must still have mastery of Arabic language and all knowledge related to the interpretation of the Qur'an; secondly, hermeneutics moves indirectly to the Qur'an, by studying the books of interpretation critically and deeply, in the hope that the previous Mufassir still leaves a space, so that it can be filled with hermeneutic studies